PENGARUH KECERDASAN INTELEKTUAL (IQ), EMOSIONAL (EI) DAN SPIRITUAL (SI) TERHADAP AGRESIVITAS PADA MAHASISWA UIN MALANG - Rahmat Aziz, Retno Mangestuti (El-QUDWAH, 2006)
The purpose of this research is to study the influence of Intelligent Quotient (IQ), Emotional Intelligence (EI), Spiritual intelligence (SI) towards the agresivity  to university student. The subjects in this research were 304 student of Islamic State University in Malang, using proportional random sampling technique, with the result that representative and balance each faculty. The instrument used in this research are IQ test and psychologist scale. Psychologist scale are spiritual intelligence scale, emotional intelligence scale, and agresivity scale. The data were analyzed using analysis of regression with SPSS version 10.0 for windows. The research result show: Three kinds of intelligence toward the agresivity are 32,5%, with spiritual intelligence (-548), emotional intelligence (-355), and IQ (-116). A good idea to help agresivity problem with developing many kinds of intelligence, specially spiritual intelligence and emotional intelligence.Key word: Intelligent Quotient, Spiritual Intelligence, Emotional  Intelligence, agresivity.